After Pascal's Wager: on religious belief, regulated and rationally held. - Warman, Jack; Efird, David (International Journal for Philosophy of Religion, 2021)
In Pascal's famous wager, he claims that the seeking non-believer can induce genuine religious belief in herself by joining a religious community and taking part in its rituals. This form of belief regulation is epistemologically puzzling: can we form beliefs in this way, and could such beliefs be rationally held? In the first half of the paper, we explain how the regimen could allow the seeking non-believer to regulate her religious beliefs by intervening on her evidence and epistemic standards. In the second half of the paper, we argue that regulated religious beliefs can be rationally held.